Agroecological Practices in Urban Fringes of the Global South: Experiences in India and Brazil - Maia , Victória Pansani Silveira; Pina , Silvia Aparecida Mikami Gonçalves (Technical and Scientific Journal Green Cities, 2025)
Objective – To identify the challenges, potentialities, and strategies for implementing agroecological practices in urban fringes. Methodology – Case study: the research analyzes experiences of Urban and Peri-Urban Agriculture (UPA) in India (Bangalore, Hyderabad, and Visakhapatnam) and an Agroforestry System (AFS) in the Comunidade Feminista Menino Chorão (CFMC) in Campinas, Brazil, through literature review and document analysis of the Indian cases, and participant observation in the CFMC case. Originality/relevance – The article contributes to the debate on Nature-Based Solutions (NbS) and climate adaptation, exploring how agroecological experiences in urban fringes can strengthen socio-environmental resilience. Its originality lies in the comparison between Global South contexts, revealing parallels and contrasts between UPA practices in India’s technological territories and a community-based initiative in vulnerable Brazilian territories. Results – The analyzed cases reveal common obstacles, such as land tenure insecurity, real estate pressures, lack of specific public policies, and uneven community engagement. Conversely, they also highlight potentialities, including care networks, food resilience, low-cost agroecological practices, community gardens, adaptive agroforestry systems, and environmental education. In both contexts, urban agricultural practices stand out as instruments of food sovereignty, environmental regeneration, and resistance to territorial exclusion. Theoretical/methodological contributions – The study broadens the understanding of the application of AFS and UPA as green infrastructures and climate adaptation strategies for cities, offering an analytical framework that integrates territorial, social, and environmental dimensions. Methodologically, it demonstrates the relevance of combining international and local qualitative experiences to identify replicable strategies for public policy. Social and environmental contributions – The experiences emphasize the importance of agroecological practices in expanding food security, strengthening community bonds, and promoting climate adaptation in vulnerable territories. They also reinforce the need for institutional support and public policies to ensure recognition and continuity of such practices.